2018
DOI: 10.1007/s00726-018-2630-7
|View full text |Cite
|
Sign up to set email alerts
|

Membrane affinity and fluorescent labelling: comparative study of monolayer interaction, cellular uptake and cytotoxicity profile of carboxyfluorescein-conjugated cationic peptides

Abstract: Fluorescent labelling is a common approach to reveal the molecular details of cellular uptake, internalisation, transport, distribution processes in biological systems. The conjugation with a fluorescent moiety might affect relevant physico-chemical and in vitro transport properties of the bioactive component. A representative set of seven cationic peptides-including cell-penetrating peptides as well as antimicrobial peptides and synthetic derivatives-was selected for our comparative study. Membrane affinity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

6
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 55 publications
2
10
0
Order By: Relevance
“…The other peptides' membrane affinity then gradually increased. This shows agreement with our previous results, where the membrane affinity order of the peptides almost followed their hydrophobicity [37]. Transportan, CM15 and Magainin are shown to be the most hydrophobic ones in the present set, according to their Rt (>12) and H (< 0) values.…”
Section: Interaction Of Peptides and Inh-peptide Conjugates With Lipisupporting
confidence: 93%
“…The other peptides' membrane affinity then gradually increased. This shows agreement with our previous results, where the membrane affinity order of the peptides almost followed their hydrophobicity [37]. Transportan, CM15 and Magainin are shown to be the most hydrophobic ones in the present set, according to their Rt (>12) and H (< 0) values.…”
Section: Interaction Of Peptides and Inh-peptide Conjugates With Lipisupporting
confidence: 93%
“…However, the ratio for most of the Dau-conjugates with tuftsin derivatives is below 100% at 50 μM (Figure S21). This shows the obvious fact that labeling molecules also have a role in the internalization processes and it can cause a significant difference in the uptake of the same peptide derivative (Dau can also be considered as a labeling molecule) . However, mostly similar conclusions can be drawn if we compare the different conjugates to each other: the uptake rates of Dau-SynB3-conjugates were significantly higher than the uptake rates of most Dau-tuftsin-conjugates; the rate of the tandem conjugates resembled or was slightly lower than the rate of Dau-Aoa-SynB3.…”
Section: Results and Discussionmentioning
confidence: 76%
“…As one dye molecule was coupled to each peptide, the fluorescence properties and the cellular uptake values are comparable. Previous investigation on a set of representative peptides demonstrated that the Cf labeling did not modify the tendency compared with those of unlabeled peptides in case of internalization rate as a consequence of altered lipophilicity and charge.…”
Section: Methodsmentioning
confidence: 96%